2019
DOI: 10.1175/jtech-d-18-0223.1
|View full text |Cite
|
Sign up to set email alerts
|

A Method on Estimating Time-Varying Vertical Eddy Viscosity for an Ekman Layer Model with Data Assimilation

Abstract: Temporal vertical eddy viscosity coefficient (VEVC) in an Ekman layer model is estimated using an adjoint method. Twin experiments are carried out to investigate the influences of several factors on inversion results, and the conclusions of twin experiments are 1) the adjoint method is a capable method to estimate different kinds of temporal distributions of VEVCs; 2) the gradient descent algorithm is better than CONMIN and L-BFGS for the present problem, although the posterior two algorithms perform better o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…As indicated by Zhang and Lu (2010) and Zhang et al. (2019), the steepest descent method is as efficient and useful as the limited‐memory conjugate gradient algorithm and the limited‐memory Broyden‐Fletcher‐Goldfarb‐Shanno algorithm that have been widely used (Alekseev et al., 2009; Zou, Navon, et al., 1993), which may be due to the clustering of eigenvalues in the spectrum of the problem being minimized (Alekseev et al., 2009). When the BFC is assumed to be spatially varying or temporally varying, ptrue→ is the vector of the spatially varying BFC or temporally BFC arranged in a sequence, as shown in Zhang et al.…”
Section: Models and Observationsmentioning
confidence: 72%
See 1 more Smart Citation
“…As indicated by Zhang and Lu (2010) and Zhang et al. (2019), the steepest descent method is as efficient and useful as the limited‐memory conjugate gradient algorithm and the limited‐memory Broyden‐Fletcher‐Goldfarb‐Shanno algorithm that have been widely used (Alekseev et al., 2009; Zou, Navon, et al., 1993), which may be due to the clustering of eigenvalues in the spectrum of the problem being minimized (Alekseev et al., 2009). When the BFC is assumed to be spatially varying or temporally varying, ptrue→ is the vector of the spatially varying BFC or temporally BFC arranged in a sequence, as shown in Zhang et al.…”
Section: Models and Observationsmentioning
confidence: 72%
“…where γ is the step size; l is the lth iteration step of the parameter estimation;  p is the vector of the spatially and temporally varying BFCs arranged in a sequence;  q is the gradient vector of the cost function with respect to  p; and q max is the  L norm of  q. As indicated by Zhang and Lu (2010) and Zhang et al (2019), the steepest descent method is as efficient and useful as the limited-memory conjugate gradient algorithm and the limited-memory Broyden-Fletcher-Goldfarb-Shanno algorithm that have been widely used (Alekseev et al, 2009;, which may be due to the clustering of eigenvalues in the spectrum of the problem being minimized (Alekseev et al, 2009). When the BFC is assumed to be spatially varying or temporally varying,  p is the vector of the spatially varying BFC or temporally BFC arranged in a sequence, as shown in Zhang et al (2011).…”
Section: Estimation Of Bfc Using the Adjoint Methodsmentioning
confidence: 99%
“…The main purpose of this is to estimate time-varying WSDCs in this study. As mentioned above, the time-varying eddy viscosity has been studied in previous studies, such as Zhang et al [21]. Therefore, we set the eddy viscosity as a variable that only varies with depth.…”
Section: Estimation Of Wsdcs With Different Distributionsmentioning
confidence: 99%
“…Cao et al [20] proposed an estimation scheme to evaluate the eddy viscosity profile (EVP) at the bottom of the Ekman boundary layer based on the adjoint method. Zhang et al [21] successfully inverted the time-varying vertical eddy viscosity coefficients in the Ekman model and also found that the inversion results were much more sensitive to the observations in the upper layers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the study of parameter estimation in atmospheric, oceanic, or coupled models is evolving rapidly in the development of assimilation methods [15][16][17][18]. Parameter estimation is mainly implemented by two methods: the variational method [10,[18][19][20][21][22][23] and ensemble Kalman filter (EnKF) [11,12,21,24,25]. Deriving the linear tangent and adjoint model, the four-dimensional variational method is difficult, even impractical, when implemented in fully coupled circulation models [19,21].…”
Section: Introductionmentioning
confidence: 99%